KOMPETENSI PENYULUH PERTANIAN DI TUJUH KECAMATAN DI KABUPATEN BEKASI, JAWA BARAT - Ridwan Kurniawan; Amri Jahi (Jurnal Penyuluhan, 2005)
Agricultural Extension agents must acquire certain competencies so as to perform well in doing their jobs. Competencies were the combination of knowledge, skills and abilities. Competencies both had intellectual as well as practical dimensions that were served as the bases of the agents’ professional expertise, especially in promoting their clientele well being. As knowledge, technology and work environment changed, the Agricultural agents should also adjust their competencies. In this conjunction, the Agricultural agents’ working environment in the seven sub-districts in the district of Bekasi had tremendously changed in the last thirty years. A vast area of well-irrigated rice fields had been converted into industrial as well as urban estates. This in turn created a lot of small and land less farmers who no longer practice rice cultivation as before. Consequently, the agents’ client profiles were subsequently changed as well. The research question then, “What were the Agricultural Agents’ needed competencies so as to serve these people well?” To address this question, a descriptive study was implemented in those sub-districts. Twenty-six Agricultural Agents were interviewed. The obtained results pointed out that the agents perceived that: (1) Extension Program Development, (2) Promotion of Farmers’ Participation, (3) Conducting Education for Farmers, (4) Organizing Farmers, (5) Agricultural Information, (6) Socio-economic aspects of Agriculture, (7) Agricultural Subject Matter, and (8) Communication, as the competencies that they needed.